Efeitos da inibição da óxido nítrico sintase neuronal sobre as respostas cardiovasculares causadas pela estimulação de receptores colinérgicos nos Núcleos do Tracto Solitário de ratos não anestesiados - Silva, Liana Gouveia da [UNIFESP] (2009)
The Nucleus of the Solitary Tract is the first sites of cardiovascular reflex afferent terminations in the central nervous system (CNS). Acetylcholine (ACh) is present within neurons and terminals in the NTS and its participation in modulation of neurovegetative function was suggested since the 80´s. However, most part of the studies in literature was performed in vitro and there were no evidences in nonanesthetized rats. Previous studies of our laboratory showed that ACh microinjection into the NTS of non-anesthetized rats elicits dose-dependent hypotension and bradicardia; and NO from nNOS may have a role in modulating these responses. Peripheral blockade of cholinergic muscarinic receptors (i.v. injection of methylatropine) did not alter hypotension induced by microinjection of ACh into the NTS of non-anesthetized rats, indicating that the activation of cholinergic system in the NTS elicits reduction of the sympathetic component. In order to discriminate cardiovascular responses elicited by cholinergic receptors stimulation in the NTS, we performed the dose-response curves for selective agonists nicotine (NIC) and pilocarpine (PIL) microinjected into the NTS of non-anesthetized rats. In addition, we investigated whether inhibition of the nNOS in the NTS affects the responses caused by cholinergic agonists. Male Wistar rats were prepared according to the methodology of guide cannulas implantation in the direction of the NTS for microinjection in freely-moving rats; and recording of blood pressure in nonanesthetized rats. Unilateral nicotine microinjection in the NTS of non-anesthetized rats caused dose-dependent hypotension and bradicardia. Microinjection of the muscarinic agonist (pilocarpine) in the NTS of non-anesthetized rats elicited significant hypotension and bradicardia, and with doses higher than 1nmol/ 100 nL it was observed hypotension followed by an increased in arterial pressure, and bradicardia. Blockade of neuronal nitric oxide syntase (nNOS) (TRIM 13.3 nmol/ 100 nL), in the NTS, significantly reduced responses elicited by nicotine and pilocarpine. Microinjection of TRIM also inhibited the increase in arterial pressure elicited by PIL 5 nmol/ 100 nL. These results are the first functional evidence in non-anesthetized rats of cholinergic receptors participation in ACh transmission s in the NTS. Differences observed with selective stimulation of cholinergic receptors in the NTS suggest the participation of each receptor subtype in modulation of distinct pathways of stimulus of cardiovascular integration to the NTS. Finally, the physiological effects of cholinergic transmission in the NTS are still unclear and NO modulation of this system remains to be elucidated.